Motor Development of Kindergarten Children - Achmat Taufiq; Eva Latipah (Penerbit Hellow Pustaka, 2025)
Character education is an important element in shaping the emotional stability of junior high school students, especially amidst the complex emotional development challenges of adolescence. Values such as empathy, self-control, and responsibility instilled through character education help students manage emotions, improve social relationships, and deal constructively with academic and social pressures. This article examines the role of character education based on a literature review, highlighting collaboration between school, family and community as key supporting elements. Despite implementation challenges, such as time constraints and lack of teacher training, a holistic approach and integration of character values in the curriculum have been shown to be effective in supporting students' emotional development. The findings provide insights for educators and policy makers to optimise the positive impact of character education in shaping adolescent emotional stability